An ISM Based Approach for Product Innovation Using a Synthesized Process. (14th September 2014) - Wang, Ming-Tang; Wu, Chang-Tzuoh; Chen, Rain; Chen, Wen-Liang; Liu, Chien-Yu
Abstract : Internet shopping has become a global business activity; it also increases the workload of delivery services. The Transnet logistics can easily deliver and collect cargos from everywhere, with difficulty of having the greatest efficiency. This study is composed of four parts; the first step of identifies opportunities in which proposing an auxiliary vehicle for Transnet truck to support service in narrow or crowded road. A weight calculation system determined the relative value of different items and applied the interpretive structural model (ISM) to modularize SET for constructing innovation from integrated new product development (iNPD). From finding GAPs in opportunities of search results are explored an innovative light electric carrier as an auxiliary vehicle is determined. The second part consists of quantifying 21 items based upon 7 specific attributes for user orientation. The third part describes a new kind of light electric vehicle which is developed and mounted on the rear side of transport trucks; it can be used to deliver goods along narrow roads. Finally, more specific details of a collapsible electric motor carrier with a battery that is recharged using truck's power system after using it are presented. The results of this study establish a research and product design to help Transnet drivers by improving carrying efficiency in narrow and crowded roads.